2020
DOI: 10.1111/ppa.13259
|View full text |Cite
|
Sign up to set email alerts
|

Impact of push–pull cropping system on pest management and occurrence of ear rots and mycotoxin contamination of maize in western Kenya

Abstract: Push–pull involves intercropping of cereals with Desmodium as a “push” crop and planting Napier grass/Brachiaria as the “pull” crop at the border. The technology has been reported to effectively control stemborers, striga weed, and fall armyworm (FAW), and to improve soil nutrition, resulting in increased grain yield. This study evaluated the impact of stemborer and FAW management using this technology on incidence of maize ear rots and preharvest contamination of grains with aflatoxin and fumonisin in western… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 34 publications
(56 reference statements)
2
22
0
Order By: Relevance
“…Moreover, the technology provides other ecological benefits contributing to improved cereal crops yield, including nitrogen fixation by Desmodium, soil structure improvement and a mulching effect in the fields. Finally, the technology reportedly reduced the incidence of human pathogenic fungal toxins in maize kernels (Njeru et al 2020;Owuor et al 2018). In addition, both Desmodium and the trap crops are a reliable source of animal fodder, particularly in drought periods, as farmers do not uproot them between farming seasons (Khan et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the technology provides other ecological benefits contributing to improved cereal crops yield, including nitrogen fixation by Desmodium, soil structure improvement and a mulching effect in the fields. Finally, the technology reportedly reduced the incidence of human pathogenic fungal toxins in maize kernels (Njeru et al 2020;Owuor et al 2018). In addition, both Desmodium and the trap crops are a reliable source of animal fodder, particularly in drought periods, as farmers do not uproot them between farming seasons (Khan et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Urb. Recently, Njeru et al [ 39 ] reported a reduction of more than 50% of fall armyworm infestation in the same Push–Pull system. In the current study, the greatest reductions in Fall Armyworm incidence and severity were recorded in the MIIC, TC, MIID, MC, MIIT and MD systems ( Table 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…The maize-desmodium push-pull intercropping system, originally developed to reduce stem borer impacts , has evidently very pronounced below-ground bene ts, including control of the parasitic weed striga, increase in soil carbon and fertility through perenniation and nitrogen xation (Khan et al 2016;Midega et al 2018), and a lower incidence of mycotoxin-producing fungal infection (Owuor et al 2018;Njeru et al 2020). By virtue of the long-term cropping plots managed by ICIPE, long-term push-pull and monoculture plots (more than 14 years old) are exquisitely suited for studies on long-term effects of legume intercropping on soil microbiomes.…”
Section: Discussionmentioning
confidence: 99%
“…Recent papers reported lower incidences of maize ear rot and associated mycotoxins (a atoxins and fumonisins) (Owuor et al 2018) as well as lower rate of infection of maize kernels with Fusarium verticillioides and Aspergillus avus (Njeru et al 2020) in smallholder farmers' push-pull plots compared to monoculture. Push-pull thus appears to promote food safety by reducing the risk of mycotoxins entering the human food chain, although the mechanisms remained unclear.…”
Section: Differential Abundance Of Taxa and Their Potential Functionamentioning
confidence: 99%
See 1 more Smart Citation